Restoration of Missing Upper Anterior Teeth Using Dental Implant: A Case Report - Jundaeng, Jarupat (Journal of The Department of Medical Services, 2022)
A 44-year-old Thai female patient with a removable denture came to see a dentist at WangHin Hospital, SisaketProvince, for a dental implant consultation. The patient had a history of having the upper anterior teeth extracted ayear ago due to a car accident. Upon the oral and the radiographic examinations, the upper right central and lateralincisors were absent, and a minor alveolar bone resorption and ridge deficiency were found. However, the woundis completely healed. Since this area is an esthetic zone, a treatment plan was made and practiced using a surgicaldental implant placement with the papilla preservation flap technique along with the bone augmentation usingalloplast. This treatment was done to prevent peri-implant bone resorption and create the emergence profile ofsurrounding the soft tissue contour, then the final restoration with crowns was done. After 3 months of treatment,it was found that the patient had a good oral hygiene and a normal surrounding gingiva. In addition, the alignment,color, and contour of the crowns harmonized with the natural teeth. In conclusion, the restoration of missing upperanterior teeth using dental implant and bone augmentation was one of the treatment choices that can solve theproblem in patients with alveolar ridge deficiency. It can also improve the patient’s occlusion function and estheticpersonality as well.